For a better world : the Winnipeg General Strike and the workers' revolt - Naylor, James, 1954-; Hinther, Rhonda L., 1974-; Mochoruk, Jim, 1957- (University of Manitoba Press, 2022)
"Canada's largest and most famous example of class conflict, the Winnipeg General Strike, redefined local, national, and international conversations around class, politics, region, ethnicity, and gender. The Strike's centenary occasioned a re-examination of this critical moment in working-class history, when 300 social justice activists, organizers, scholars, trade unionists, artists, and labour rights advocates gathered in Winnipeg in 2019. Probing the meaning of the General Strike in new and innovative ways, For a Better World includes a selection from the conference as well as others contributions. Editors Naylor, Hinther, and Mochoruk depict key events of 1919, detailing the dynamic and complex historiography of the Strike and the larger Workers' Revolt that reverberated around the world and shaped the century following the war. The chapters delve into intersections of race, class, and gender. Settler colonialism's impact on the conflict is also examined. Placing the struggle in Winnipeg within a broader national and international context, several contributors explore parallel strikes in Edmonton, Crowsnest Pass, Montreal, Kansas City, and Seattle. For a Better World interrogates types of commemoration and remembrance, current legacies of the Strike, and its ongoing influence. Together, the essays in this collection demonstrate that the Winnipeg General Strike continues to mobilize--revealing our radical past and helping us to think imaginatively about collective action in the future."-- Provided by publisher.
Some chapters based on papers selected from the Winnipeg General Strike Centenary Conference: Building a Better World - 1919/2019, held from May 9-11, 2019.
Keywords: General Strike, Winnipeg, Man., 1919.; Grève générale, Winnipeg, Man., 1919.; HISTORY / Canada / Provincial, Territorial & Local / Prairie Provinces (AB, MB, SK).; Manitoba -- Winnipeg; 1919; Winnipeg General Strike.; labour relations.; Electronic books.